Relationship Between Health-Related Quality of Life (HRQoL) Factors in Patients With Diabetes Mellitus : A Literature Review - Satyafebrianti, Kendra Callista; Santoso, Aktaruddin Arief (Faculty of Medical - UPN Veteran Jawa Timur, 2025)
Background: Diabetes mellitus (DM) is a chronic disease that can significantly affect the quality of life of patients. Poor quality of life is often associated with poor disease control, complications, and psychosocial burden. A better understanding of the factors that affect the quality of life of DM patients is essential for designing effective interventions. Objective: This study aims to analyze the relationship between health-based quality of life factors and the condition of diabetes mellitus patients. Method: This study used a literature review method. Researchers collect data through database sources, such as PubMed, Google Scholar, and ScienceDirect. The articles used are in English. The keywords used in the article search are: